1995
DOI: 10.1093/ajcn/62.6.1527s
|View full text |Cite
|
Sign up to set email alerts
|

Novel urinary metabolite of alpha-tocopherol, 2,5,7,8-tetramethyl-2(2’-carboxyethyl)-6-hydroxychroman, as an indicator of an adequate vitamin E supply?

Abstract: Previously, the metabolism of alpha-tocopherol was considered to involve the opening of the chroman structure because of its oxidation to tocopherylquinone. In contrast, we describe here 2,5,7,8-tetramethyl-2(2'-carboxyethyl)-6-hydroxychroman (alpha-CEHC) as the major urinary metabolite of alpha-tocopherol that appears in human urine after vitamin E supplementation. It is formed directly from alpha-tocopherol without previous oxidative splitting of the chroman ring. The correlation of alpha-tocopherol intake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
200
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(212 citation statements)
references
References 18 publications
10
200
0
1
Order By: Relevance
“…1A) revealed, that the a-tocopherol content was consistently lower than that of human serum, which usually ranges between 20 and 30/zM. 27 Some of the 10 different sera tested (Fig. 1A) even had a-tocopherol contents of less than 10 nM, which was our detection limit.…”
Section: ~-Tocopherol and Selenium Content Of Commercially Available mentioning
confidence: 78%
“…1A) revealed, that the a-tocopherol content was consistently lower than that of human serum, which usually ranges between 20 and 30/zM. 27 Some of the 10 different sera tested (Fig. 1A) even had a-tocopherol contents of less than 10 nM, which was our detection limit.…”
Section: ~-Tocopherol and Selenium Content Of Commercially Available mentioning
confidence: 78%
“…Together, these data suggest the modest increase in lung α-CEHC levels is likely a result of plasma delivery and not metabolism of α-tocopherol in situ. Presumably, the increase in kidney α-CEHC levels is due to its excretory function [2,27]. However, since CYP4F1 is constitutively expressed in the kidney, α-tocopherol metabolism within the kidney may be an additional source of kidney α-CEHC.…”
Section: Discussionmentioning
confidence: 99%
“…Only α-tocopherol, not the others, is maintained in human plasma and tissues, as a result of the function of the hepatic α-tocopherol transfer protein (α-TTP) [1]. Unlike other fat-soluble vitamins, vitamin E is not accumulated in the body to toxic levels, suggesting that mechanisms, i.e., metabolism and excretion, prevent excess accumulation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The data furthermore showed that the a-tocopheryl quinone arising from excessive oxidative degradation of a-tocopherol can potentially interfere with mitochondrial electron transfer (Gregor et al 2006). Searching for urinary metabolites of vitamin E, another metabolite of a-tocopherol, 2,5,7,8-tetramethyl-2(2 0 -carboxyethyl)-6-hydroxychroman (a-CEHC), was identified (Schultz et al 1995). The metabolites of vitamin E are the CEHC products of the respective forms of vitamin E, that is, a-, b-, c-, and d-CEHC, and the various non-a-tocopherol forms are metabolized in preference to a-tocopherol (Swanson et al 1999;Sontag and Parker 2002).…”
Section: Vitamin E Form and Functionmentioning
confidence: 99%